The river we remember : a novel [large type] - Krueger, William Kent (Thorndike Press large print top shelf., 2023)
"On Memorial Day, as the people of Jewel, Minnesota gather to remember and honor the sacrifice of so many sons in the wars of the past, the half-clothed body of wealthy landowner Jimmy Quinn is found floating in the Alabaster River, dead from a shotgun blast. Investigation of the murder falls to Sheriff Brody Dern. As suspicions and accusations mount and the town teeters on the edge of more violence, Dern struggles to find the truth. Caught up in the torrent of anger are a war widow and her adolescent son, the publisher of the local newspaper, an aging deputy, and a crusading female lawyer, all of whom harbor secrets that Quinn's death threatens to expose"--